2010
DOI: 10.1134/s0006297910040115
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of glycoprotein E C-End of West Nile virus and evaluation of its interaction force with αVβ3 integrin as putative cellular receptor

Abstract: Recombinant polypeptide containing the 260-466 amino acid sequence of West Nile virus (WNV) strain LEIV-Vlg99-27889-human glycoprotein E (gpE, E(260-466)) was constructed. Immunochemical similarity between the E(260-466) and gpE of WNV was proven by enzyme immunoassay (EIA), immunoblot, competitive EIA, hemagglutination inhibition, and neutralization tests using polyclonal and monoclonal antibodies against the viral gpE and recombinant E(260-466). Polypeptide E(260-466) induced formation of virus neutralizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
0
19
0
2
Order By: Relevance
“…24 In the present study, similar mechanisms could underlie the association between blood group A and symptomatic WNV disease. Indeed, it was shown that WNV interacts with LBP and αVβ3 integrin at the cell surface of host cells through its E glycoprotein, 47, 48 and blood group A antigen could serve as a co-receptor for WNV. This would explain the findings that subjects with blood group A demonstrated higher viral loads in whole blood than subjects with other blood groups, 14 however, this would not explain why the same assoication is not observed for subjects with blood group AB, whose erythrocytes express approximately half of the number of A sites than A erythrocytes 49 and this would not explain the association with Rh(D)-negativity.…”
Section: Discussionmentioning
confidence: 99%
“…24 In the present study, similar mechanisms could underlie the association between blood group A and symptomatic WNV disease. Indeed, it was shown that WNV interacts with LBP and αVβ3 integrin at the cell surface of host cells through its E glycoprotein, 47, 48 and blood group A antigen could serve as a co-receptor for WNV. This would explain the findings that subjects with blood group A demonstrated higher viral loads in whole blood than subjects with other blood groups, 14 however, this would not explain why the same assoication is not observed for subjects with blood group AB, whose erythrocytes express approximately half of the number of A sites than A erythrocytes 49 and this would not explain the association with Rh(D)-negativity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that host surface glycoproteins interact with the viral envelope proteins to initiate attachment (Chen et al, 1997b; Kroschewski et al, 2003; Davis et al, 2006). Attachment might also be mediated by integrins, cytoskeleton proteins, and cholesterol-dependent lipid raft pathways (Medigeshi et al, 2008; Bogachek et al, 2010). Internalization is then mediated by clathrin-coated vesicles (Chu and Ng, 2004).…”
Section: The Flavivirus Infectious Cyclementioning
confidence: 99%
“…Cellular α v β 3 integrin and laminin-binding protein were reported to function as WNV receptors [17,18] but the use of α v β 3 integrin as a WNV receptor was not consistently supported by data from subsequent studies. Even though several flaviviruses including WNV contain an integrin recognition RGD/RGE motif within the domain III region of their E proteins, RGD peptides did not competitively inhibit WNV entry [17].…”
Section: Virion Morphology Attachment and Entrymentioning
confidence: 99%